1999
DOI: 10.1177/109861119900200401
|View full text |Cite
|
Sign up to set email alerts
|

To Acquiesce or Rebel: Predicting Citizen Compliance with Police Requests

Abstract: This article explores a variety of predictors of citizens' compliance with police requests to cease misbehavior. Where possible, the authors attempt to closely replicate the 1996 model formulated by Mastrofski, Snipes, and Supina to explain citizen compliance in Richmond, Virginia. Data on police-citizen encounters (N = 989) are drawn from the Project on Policing Neighborhoods, conducted in Indianapolis, Indiana, and St. Petersburg, Florida. The analysis indicates that a variety of legitimating factors influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
124
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(134 citation statements)
references
References 34 publications
8
124
0
2
Order By: Relevance
“…For example Mastrofski, Snipes, and Supina (1996, p.269) examined police-citizen encounters and found that compliance with police was related to "the legitimacy of the police intervention." McCluskey, Mastrofski and Parks (1999) found similar results in their study of police-citizen encounters, highlighting the importance of legitimacy to compliance. Sunshine and Tyler (2003) and Tyler and Fagan (2008) also demonstrate that legitimacy is not only related to compliance but to the…”
Section: Background For the Reviewsupporting
confidence: 66%
“…For example Mastrofski, Snipes, and Supina (1996, p.269) examined police-citizen encounters and found that compliance with police was related to "the legitimacy of the police intervention." McCluskey, Mastrofski and Parks (1999) found similar results in their study of police-citizen encounters, highlighting the importance of legitimacy to compliance. Sunshine and Tyler (2003) and Tyler and Fagan (2008) also demonstrate that legitimacy is not only related to compliance but to the…”
Section: Background For the Reviewsupporting
confidence: 66%
“…More generally, people accept the decisions of police when they believe the police have acted fairly and openly with them (Tyler & Huo, 2002). On the other hand, observational studies of onstreet encounters find that experiencing disrespect from the police reduces citizen compliance with police instructions (Mastrofski, Snipes, & Supina, 1996;McCluskey, Mastrofski, & Parks, 1999). McCluskey (2003) found that, controlling for other factors, citizens who receive respectful treatment are observed to be twice as likely to comply, and those receiving disrespectful treatment are nearly twice as likely to rebel.…”
Section: Discussionmentioning
confidence: 99%
“…All but one of these studies relied on the data coded by observers according to the observation instrument, and so the indicators of procedural justice were somewhat limited. For example, the initial study and the replication of that study (McCluskey et al 1999) both operationalized voice or participation in terms of whether a citizen rather than police initiated the encounter (e.g., by flagging down the officer in the field, or placing a phone call to 911 or another police number); this of course leaves open the extent to which the citizen is given an opportunity by the officer at the scene to tell his/her story. The quality of interpersonal treatment was measured only as police disrespect toward the citizen, and trustworthy motives were captured only as police treating the citizen as having a situational status other than that of suspected offender.…”
Section: Police Requests and Citizen Compliancementioning
confidence: 99%
“…First, research suggests that citizens who see the police as legitimate are, in their interactions with the police, more likely to comply with police commands, directions, and requests. In the micro-context of police-citizen encounters, citizens' compliance makes the performance of police tasks easier (Mastrofski, Snipes, and Supina 1996;McCluskey 2003;McCluskey, Mastrofski, and Parks 1999), and can be expected to result in less use of force by police and fewer injuries to both police and citizens. Second, citizens who see the police as legitimate might be expected to more readily cooperate with police and other legal actors, for example, in reporting crime, and perhaps in providing information (Hart and Rennison 2003).…”
Section: Police Legitimacy and Pro Cedur Al Justicementioning
confidence: 99%